2017
DOI: 10.21037/atm.2017.11.22
|View full text |Cite
|
Sign up to set email alerts
|

Novel venous thromboembolic disease (VTED) prophylaxis for total knee arthroplasty—aspirin and fish oil

Abstract: Background: Despite the demonstrated success of multiple anticoagulation therapies for post-operative prophylaxis of thromboembolic disease in lower extremity arthroplasties, each modality comes with a unique set of limitations. Thus, the ideal anticoagulation medication which provides adequate therapy with minimal cost, complications, or added patient work is yet to be defined. One promising novel thrombophylactic supplement is fish oil, as many preliminary clinical trials have demonstrated a protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Bonutti et al reported on a prospective, nonrandomized study of orthopedic patients undergoing total knee arthroplasty (n = 850) receiving aspirin plus a pulsatile compression stocking, rivaroxaban, or a combination of aspirin and fish oil. The occurrence of DVT was significantly lower in the aspirin plus fish oil group versus aspirin plus stocking (0.33% vs. 7%; odds ratio 0.045; P < 0.05), and not different from that in the rivaroxaban group (1%) (111). Larger prospective, randomized, and double-blind studies are needed to determine whether omega-3 supplements have a beneficial impact on VTE.…”
Section: Translation: Developing a Platform For Pro-resolving Vasculamentioning
confidence: 88%
“…Bonutti et al reported on a prospective, nonrandomized study of orthopedic patients undergoing total knee arthroplasty (n = 850) receiving aspirin plus a pulsatile compression stocking, rivaroxaban, or a combination of aspirin and fish oil. The occurrence of DVT was significantly lower in the aspirin plus fish oil group versus aspirin plus stocking (0.33% vs. 7%; odds ratio 0.045; P < 0.05), and not different from that in the rivaroxaban group (1%) (111). Larger prospective, randomized, and double-blind studies are needed to determine whether omega-3 supplements have a beneficial impact on VTE.…”
Section: Translation: Developing a Platform For Pro-resolving Vasculamentioning
confidence: 88%
“…Thirdly, omega 3 fatty acids have been shown to possess antiarrhythmic properties that could be clinically beneficial 46. Finally, studies have reported that fish oil can reduce thrombosis 47. Additionally, studies have reported that the anti-inflammatory properties of fish oil could have a preventive role in the pathophysiology of CVD outcomes 1148.…”
Section: Discussionmentioning
confidence: 99%
“…34 While the reduced risk of venous thromboembolism with use of cod liver oil capsules has been reported previously, to the best of our knowledge, use of bendroflumethiazide has not been associated with a decreased risk of venous thromboembolism. 35,36 While it is plausible that glucocorticoid and antidepressant use contribute to our findings that asthma, osteoarthritis, and depression are associated with increased risk of venous thromboembolism, accounting for common disease-specific medications does not reduce the likelihood of venous thromboembolism considerably. Alternatively, we provide evidence that the apparent protective effects of hypercholesterolemia and diabetes in this cohort are likely due to use of disease-specific therapies.…”
Section: Discussionmentioning
confidence: 73%